PERSEPSI BIROKRASI TERHADAP KEPEMIMPINAN BUPATI AHMAD MARZUQI DI KABUPATEN JEPARA - Akhsan Fakih .; Purwoko . .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
The purpose of this study was to determine the perception of the bureaucracy against the district head Ahmad Marzuqi in Jepara district, with indicators; 1) the perception of bureaucracy to figure Ahmad Marzuqi regent; 2) perception of the bureaucracy against the Regent Ahmad Marzuqi ability to communicate; 3) perceptions of ability in the ability to take policy; 4) perceptions of the ability to excite or motivate subordinates; and 5) the perception of the ability to establish cooperation with outside parties. This type of research is descriptive analysis and used a qualitative approach because it only intends to describe the leadership of Ahmad Marzuqi Jepara regent in perspective, so it does not require a quantitative approach requires standard size.The results showed that the leadership of Regent Ahmad Marzuqi period served as Regent of Jepara between 2012 s / d 2017 is quite good, because its action can be perceived in a positive way for the majority of the people of Jepara, good development in infrastructure, health, education and public policy developed. Based on data analysis are built according to information sources and documentation, then it is understood that: 1) The Regent Ahmad Marzuki figure Jepara Regent known as the most popular over-the regent of Jepara Regent before, as evidenced by the survey results of the Office of Information and Communications; 2) Before serving, Regent Ahmad Marzuqi has completed a Master degree as the level of formal education. Phenomena such as these have at least been able to justify their pernyaataan that higher levels of formal education a person, the higher the level of social status were successfully acquired, so the expectation is led by the mayor, with formal education, it will be able to bring a breakthrough policy of positive and innovative ; 3) Regent Ahmad Marzuki from among noble families with socio-economic tingakat high enough, so in this case can be expected to be able to create a pattern of obedience to the community leaders. It is based on the feudalistic system is quite thick and thrive in Jepara society, which regards the social status and economic status of a person is one of the references; 4) Profession of Ahmad Marzuki before this was teak furniture entrepreneurs who reside in District Keling, so sociologically have a level of social closeness (proximity) to build Jepara regency to be similar or parallel to the district / city to the other; and 5) Figure Regent Ahmad Marzuqi very popular in the public eye today Jepara, where the provision of such popularity in the elections simultaneously, the later Regent still have a high level of elektabilitas anyway.Keywords: Public Perception, district leader Ahmad Marzuqi